Static cut-points of hypertension and increased arterial stiffness in children and adolescents: The International Childhood Vascular Function Evaluation Consortium - Zhao M (WILEY, 2022)
Pediatric elevated blood pressure (BP) and hypertension are usually defined using traditional BP tables at the 90th and 95th percentiles, respectively, based on sex, age, and height, which are cumbersome to use in clinical practice. The authors aimed to assess the performance of the static cut-points (120/80 mm Hg and 130/80 mm Hg for defining elevated BP and hypertension for adolescents, respectively; and 110/70 mm Hg and 120/80 mm Hg for children, respectively) in predicting increased arterial stiffness. Using data from five population-based cross-sectional studies conducted in Brazil, China, Korea, and New Zealand, a total of 2546 children and adolescents aged 6-17 years were included. Increased arterial stiffness was defined as pulse wave velocity >= sex-specific, age-specific, and study population-specific 90th percentile. Compared to youth with normal BP, those with hypertension defined using the 2017 American Academy of Pediatrics guideline (hereafter referred to as "percentile-based cut-points") and the static cut-points were at similar risk of increased arterial stiffness, with odds ratios and 95% confidence intervals of 2.35 (1.74-3.17) and 3.07 (2.20-4.28), respectively. Area under the receiver operating characteristic curve and net reclassification improvement methods confirmed the similar performance of static cut-points and percentile-based cut-points (P for difference > .05). In conclusion, the static cut-points performed similarly well when compared with the percentile-based cut-points in predicting childhood increased arterial stiffness. Use of static cut-points to define hypertension in childhood might simplify identification of children with abnormal BP in clinical practice.